Applications of Single-Cell RNA Sequencing in Cardiovascular Research - Fan, Yu; Zhou, Han; Liu, Xuexue; Li, Jingyan; Xu, Ke; Fu, Xiaodong; Ye, Lei; Li, Guang (Frontiers in Cell and Developmental Biology, 2022)
In recent years, cardiovascular disease (CVD) continues to be the leading cause of global disease burden. Extensive efforts have been made across basic, translational, and clinical research domains to curb the CVD epidemic and improve the health of the population. The successful completion of the Human Genome Project catapulted sequencing technology into the mainstream, and aroused the interests of clinicians and scientific researchers alike. Advances in single-cell RNA sequencing (scRNA-seq), which is based on the transcriptional phenotypes of individual cells, have enabled the investigation of cellular fate, heterogeneity, and cell-cell interactions, as well as cell lineage determination, at a single-cell resolution. In this review, we summarize recent findings on the embryological development of cardiovascular system and the pathogenesis and treatment of cardiovascular disease, as revealed by scRNA-seq technology. In particular, we discuss how scRNA-seq can help identify potential targets for the treatment of cardiovascular diseases, and conclude with future perspectives for scRNA-seq.